Diagnosis of performance by the application of swimming tests - Ruzbarsky, P.; Turek, M. (Biomechanics and Medicine in Swimming X, 2006)
Determining the level of preparedness, as a significant factor in training, represents the feedback information about the current condition of an athlete. It plays an important role since it provides the information about the changes of the athlete's conditions caused by the training load and other factors with the objective to regulate the impact the training process on the athlete. To monitor the level of both endurance and pace, a set of swimming tests has been compiled. Some of the tests used by the Slovak Swimming Federation have been taken into consideration. The paper deals with the 3000 meters crawl results, which have been carried out on sample of 105 swimmers aged 13-16 years, and the 4 x 50 meters freestyle test realized on the sample of 53 swimmers aged 13-16 respectively. The average blood lactate level, when using the 3000m test, was 5,67 mmol/l for boys aged 13-14 and 4,67 mmol/l for boys aged 15-16. The blood lactate level was lower when measured for girls; 4,50 mmol/l for 13-14 years old and 3,20mmol/l for 15-16 years old, respectively. When using the 4x50m test, the values were following: boys aged 13-14 were at 0,02 mmol/l, 15-16 years old at 11,22 mmol/l, girls aged 13-14 at 10,20 mmol/l and finally, girls aged 15-16 at 10,58 mmol/l.